Some aspects of forming a healthy environment in society through the formation of passion education in youth - Raxmanova , Nazokat (The Lingua Spectrum, 2025)
Passion is a concept that expresses a predisposition to the benefits of the material world to the human psyche, through the cultivation of passion, a person achieves inner peace, reaches spiritual perfection, finds his place in society. This article examines some aspects of the formation of a healthy environment in society through the formation of passion education in youth.